Impact of farm size on the function of landscape-level payments for ecosystem services: An agent-based model study - Wu, Vince; Bell, Andrew Reid; Zhang, Wei (EarthArXiv, 2024)
Reducing pesticide use and restoring biodiversity are among the most pressing environmental challenges. Enhancing natural pest control ecosystem services through the integration of non-crop habitats (NCH) offers promising potential, creating a positive feedback loop by harnessing insect biodiversity to reduce pesticide reliance. Policy support is needed at the landscape level to encourage adoption of this currently underutilized approach, which depends on spatial coordination and collective behavioral change. Farm size, which critically influences farmers' agrochemical inputs, agroecological practices, and interactions with neighboring farms, varies across agricultural landscapes. It is unclear what role farm size plays in landscape-scale agri-environmental incentive programs, which have recently seen growing attention in scientific research and policy implementation. We employ framed field games and agent-based modeling as complementary research tools, exploring how farm size impacts the function of landscape-scale NCH subsidies aimed at encouraging coordinated provision and sharing of natural pest control services to reduce pesticide use. Our model simulation shows that, in landscapes of larger average farm size or lower farm size heterogeneity, NCH subsidies are significantly more effective at reducing pesticide use and increasing NCH efficiency in providing joint production benefits. Our results imply that landscape-scale payments for natural pest control ecosystem services face fewer obstacles as incentive-based mechanisms in landscapes of larger, more homogeneous farms, supporting the implementation of landscape-scale initiatives in such areas to effectively enhance ecosystem services. Our findings contribute to the growing discussion around landscape-level financial incentive programs that depend on spatial coordination, highlighting the importance of farmers’ land holding size.